Investigation of the biocompatibility of various pulp capping materials on zebrafish model. - Meltem Karahan; Bahar Basak Kiziltan Eliacik; Umut Cagiral; Evin Iscan; Gunes Ozhan (PLoS ONE)
Testing the biocompatibility of commercially available dental materials is a major challenge in dental material science. In the present study, the biocompatibility of four commercially available dental materials Mineral Trioxide Aggregate, Biodentine, Harvard BioCal-CAP and Oxford ActiveCal PC was investigated. The biocompatibility analysis was performed on zebrafish embryos and larvae using standard toxicity tests such as survivability and hatching rates. Comparative toxicity analysis of toxicity was performed by measuring apoptosis using acridine orange dye and whole mount immunofluorescence methods on zebrafish larvae exposed to the dental materials at different dilutions. Toxicity analysis showed a significant decrease in survival and hatching rates with increasing concentration of exposed materials. The results of the apoptosis assay with acridine orange showed greater biocompatibility of Biodentine, Oxford ActiveCal PC, Harvard BioCal-CAP and Biodentine compared to MTA, which was concentration dependent. Consequently, this study has shown that showed resin-modified calcium silicates are more biocompatible than traditional calcium silicates.